Novel chiral ionic liquids stationary phases for the enantiomer separation of chiral acid by high‐performance liquid chromatography. Issue 5 (24th February 2018) - He, Shanshan; He, Yunchao; Cheng, Lingping; Wu, Yaling; Ke, Yanxiong
Abstract: Novel chiral ionic liquid stationary phases based on chiral imidazolium were prepared. The ionic liquid chiral selector was synthesized by ring opening of cyclohexene oxide with imidazole or 5, 6‐dimethylbenzimidazole, and then chemically modified by different substitute groups. Chiral stationary phases were prepared by bonding to the surface of silica sphere through thioene "click" reaction. Their enantioselective separations of chiral acids were evaluated by high‐performance liquid chromatography. The retention of acid sample was related to the counterion concentration and showed a typical ion exchange process. The chiral separation abilities of chiral stationary phases were greatly influenced by the substituent group on the chiral selector as well as the mobile phase, which indicated that, besides ion exchange, other interactions such as steric hindrance, π‐π interaction, and hydrogen bonding are important for the enantioselectivity. In this report, the influence of bulk solvent components, the effects of varying concentration, and the type of the counterion as well as the proportion of acid and basic additives were investigated in detail. Abstract :